Step towards Enriching Frequency Support from Wind-Driven Permanent-Magnet Synchronous Generator for Power System Stability - ALI, M. A. S. (Advances in Electrical and Computer Engineering, 2022)
Wind power plants do not provide frequency support subject to disturbances because wind turbine generators (WTGs) are decoupled from system frequency deviations. To provide frequency regulation from a permanent-magnet synchronous generator-based wind energy conversion system following the change in system load demand, this paper presents a basic controller that directly perturbs the rotor-speed reference according to system frequency deviations. In the proposed approach, the kinetic energy (KE) of the rotating parts of the WTGs is utilized for frequency support, thus enriching the power system stability. The prominent aspect of opting for this concept is the immediate KE release or absorption through a step-change in the speed reference. Furthermore, the system proceeds to its normal operation without causing instability issues. To prove this concept, extensive simulations in MATLAB/Simulink have been performed, and the results demonstrate its good capability in providing system frequency regulation, resulting in the enhancement of power system stability. For comparison, simultaneous control of the power-frequency droop control and DC-link inertial support was also prepared.